First-Year Law Students’ and Teacher’s Questioning in Class - Ribeiro, Luísa; Rosário, Pedro; Moreira, Iněs; Cunha, Rosário Serrão (Frontiers in Psychology, 2019)
Classroom questioning can be considered a key factor in the promotion of student engagement. This case study explored classroom questioning practices and perceptions of a group of 47 first-year law students and their teacher. Eight lessons of 90 min were observed and audio-recorded and afterward the students and the teacher answered a questionnaire. The teacher was also interviewed. Researchers examined the number and type of questions asked by the teacher and by the students in the classroom and analyzed the students’ and the teacher’s perceptions about the importance of classroom questioning. Results indicated that the teacher and most students consider questioning important or very important for student learning. The number of questions posed by students as opposed to by their teacher was not balanced, as the teacher was responsible for 93% of the questions. The analysis of the type of questions posed by the teacher and by the students showed a predominance of low-order questions. Therefore, classroom questioning in this case study did not seem to promote students’ autonomous thinking. The current study suggests the importance of examining the teacher and students’ patterns of questioning together, analyzing its similarities and discrepancies.